Crustal and uppermost mantle structures in the frontal Himalaya and Indo-Gangetic basin using surface wave: Tectonic implications. (30th December 2017) - Kumar, Amit; Kumar, Naresh; Mukhopadhyay, Sagarika; Baidya, P.R.
Abstract: Characteristics of dispersion curves of Rayleigh and Love waves of 2005 Kashmir earthquake and its aftershocks are utilized to investigate the sub-surface structural variations within the northern margin of the Indian continent (i.e. Indo-Gangetic Plains) and the frontal part of the northwestern Himalaya. Surface waves of these earthquakes recorded in the Broad Band Seismometers (BBS) installed at Ajmer, Delhi and Shimla were used for this investigation. Estimated group velocities along three paths from earthquake source region to these stations are in the range of 2.17 km/s to 3.94 km/s which are sufficient to investigate the crustal and uppermost mantle structures. Paths covering northern margin of the Indian continent has very low group velocities for periods less than 10-s that indicate presence of thick sediments. High differences are observed between Love and Rayleigh wave group velocities for the paths crossing Himalayan wedge that can be ascribed to the effect of anisotropy due to India-Eurasia collision. The inversion of dispersion curves was performed to investigate sub-surface shear wave velocity structure and variation of anisotropy with depth for crust and uppermost mantle. A ∼6km thick sediments divided into two layers (unconsolidated and consolidated) are seen in the Indo Gangetic Plain deposited above underthrusting Indian plate. The Conrad and Moho depths increase from Ajmer, the southernmost station in the IGP to Shimla, the station lying in the Himalayan wedge. This shows the dipping geometry of the Indian plate. The average Moho depth along these paths from earthquake source to Ajmer station is 42.5 km, to Delhi station is 44 km and to Shimla station is at 46 km. Average values of Conrad depth for these ray paths are 18.5 km, 19.5 km and 26.5 km respectively. The S wave velocity along Ajmer path is higher than that along the other two paths. This may be due to lateral heterogeneity of the crust and mantle for the study area. Frontal western Himalaya is anisotropic in nature, whereas the IGP region is not. Anisotropy effect in the western Himalaya is most pronounced in the lower crustal material of the underthrusted Indian plate. It is quite large in the uppermost mantle below the frontal Himalayan region. We infer that anisotropy in the lower crust and uppermost mantle could be due to development of preferably oriented folds, faults and fractures and possible reorientation of crystals as a consequence of ongoing deformation caused by continent-continent collision.